A novel method for fabricating hybrid biobased nanocomposites film with stable fluorescence containing CdTe quantum dots and montmorillonite-chitosan nanosheets. (10th July 2016) - Guo, Yawen; Ge, Xuesong; Guan, Jing; Wu, Lin; Zhao, Fuhua; Li, Hui; Mu, Xindong; Jiang, Yijun; Chen, Aibing
Highlights: The MMT-CS/QDs solution and films possess strong fluorescence intensity. The MMT-CS/QDs solution and films present good storage stability. The fluorescence wavelength was controllable by refluxing with different time. Abstract: A method was presented for fabricating the fluorescent nanocomposites containing CdTe quantum dots (QDs) and montmorillonite (MMT)-chitosan (CS). MMT-CS/CdTe QDs nanocomposites were prepared via a simple, versatile and robust approach combination of covalent and electrostatic assembly methods (Scheme 1). The negatively charged MMT was initially modified with positively charged CS through electrostatic assembly, followed by incorporation of CdTe-QDs into the MMT-CS nanosheets by covalent connections between the amino groups of CS and the carboxylic acid groups of thioglycollic acid (TGA). The X-ray diffraction (XRD), High resolution transmission electron microscopy (HRTEM), scanning electron microscopy (SEM) and the FTIR were used to prove the QDs have intercalated into the MMT-CS matrix. The fluorescence emission spectra showed that the MMT-CS/CdTe QDs nanocomposites had the best fluorescence intensity compared with the bare CdTe QDs and CS-QDs.